Scenerio of HIV patients reported to University Kebangsaan Medical Centre during 2006-2009 (Bangladesh Journal of Medical Science, 2011)
Objective: A study was undertaken to identify the HIV-positive cases from suspected patients reported to University Kebangsaan Malaysia Medical Centre (UKMMC) from January, 2006 to December; 2009. Methods: Cases were identified and confirmed by three established sero-diagnostic tests: Micro particulate Enzyme Immunoassay, Passive Particle Agglutination Test and Line Immunoassay. Results: A total of 256 HIV positive patients were identified and highlighted about their age, sex, ethnic origin and year wise distribution of cases. Frequency distribution of HIV-positive cases among different age groups indicated that, 144 (%) were aged between 21 to 40 years, 81 (%) were aged 41 to 60, 19 (%) were aged above 60 and 12 (%) were in the age group of 0-20 years. It revealed that the highest number of HIV-positive patients was in the age group of 21-40 years. Among the 4 groups of people living in Malaysia, HIV infection was found more in Chinese community (101), followed by Malaya community (97), Other community (Sikhs, tribes, foreigners) living in Malaysia (30) and Indian community (28). A total of 179 male and 77 female were positive for HIV infection. Monthly records of case detection indicate more or less similar prevalence pattern throughout the study period. Conclusions: It reveals from the report that the Malysian patients are mostly infected at the adulthood unlike other countries where majority of infections occur in young age .A high percent of HIV infection in males in the country indicates that they might played a vital role in carrying and disseminating infectiions to their female parterners. Keywords: HIV/AIDS; Sero-diagnosis; Socio-demographic profile; Malaysia. DOI: 10.3329/bjms.v10i1.7315 Bangladesh Journal of Medical Science Vol.10 No.1 Jan 2010 pp.21-28